Mental Health and Nursing Care of Individuals with Cancer and Their Families - Fitch, Margaret (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This collection of articles provides insight into the mental health and nursing care of individuals who are confronting a life-threatening illness. As individuals face a cancer diagnosis, there will be many challenges and changes in their lives. Emotional distress can emerge to greater and lesser degrees. Frequently, these individuals will require additional assistance to cope with the emotional distress they experience. Nurses have an important role in assessing this emotional distress and providing relevant interventions.